Access to lactation consult services during the COVID-19 pandemic and the impact on breastfeeding outcome variables - Caroline Maltese; Chintan K. Gandhi; Sarah Ines Ramirez; Kristin K. Sznajder; Nicole Hackman (PLoS ONE, 2025)
Background: Inpatient lactation consultation and social influences affect breastfeeding (BF) choices and sustainability. The COVID-19 pandemic introduced barriers to BF initiation and continuation including access to lactation support and social connection. Equitable access to lactation support can reduce health disparities. Research aim: The study aimed to (1) determine the prevalence of professional lactation support during the COVID-19 pandemic, (2) explore the influence of this pandemic on the equitable accessibility to lactation support services, and (3) identify changes in BF rates and access to lactation support at three different phases of the pandemic (early, middle, and late). Methods: Patients receiving prenatal care at a mid-sized academic medical institution in Central Pennsylvania were recruited and surveyed and this data was collected and combined with data from the electronic medical record. Results: 88% of patients received a lactation consultation during birth hospitalization. Having COVID-19 during pregnancy did not change access to lactation consultation post-partum (p = 0.0961). Neither BF exclusivity during the three phases of the pandemic nor the number of lactation consult visits were statistically different (p = 0.2263; p = 0.0958 respectively). Multiple regression models assessing BF exclusivity in the hospital found significant associations with having a lactation consult (OR 2.50, 95% CI 1.04, 6.04), having an infant in the neonatal intensive care unit (OR 0.29, 95% CI 0.11, 0.73), and having reported social support during pregnancy (OR 1.09, 95% CI 1.01,1.18). Conclusions: Social support during pregnancy and having a lactation consult visit during birth hospitalization remained critical factors for BF exclusivity. This study highlights the importance of having professional lactation support on both BF exclusivity and continuation during the COVID-19 pandemic.